Motivasi Berprestasi (Achievementmotivation) Guru Dalam Melaksanakan Pembelajaran Pada Masa Pandemi Covid-19 - Rosyada Ikhwani; Ahmad Hari Witono; Abdul Kadir Jaelani (Journal of Classroom Action Research, 2022)
This research aims to find out how the state of teacher achievement motivation during the Covid 19 pandemic, because by knowing the state of teacher achievement motivation in carrying out learning then we can easily guess the performance of teachers and the continuity of learning activities during the Covid 19 pandemic whether experiencing obstacles or running smoothly. The method used in this research is a descriptive qualitative research method. The study population amounted to 10 people SDN 2 Wakul. The subjects in this study were 4 SDN 2 Wakul Teachers. Data collection uses interview techniques, documentation, and observation sheets. The data analysis technique used is an analysis technique according to Miles and Huberman, namely data collection, data condensation, data presentation, and inference. The results of this study are: First, teachers have the same focus, which is to focus on being able to convey the subject matter quickly and precisely to learners with limited teaching time during pandemics. Second, teachers at times of pandemics have not shown a desire to learn more, especially about technology. Third, during pandemics teachers often take advantage of their free time to be able to complete their work on time. Fourth, during the pandemic teachers are passionate in completing the given tasks, one of which is carrying out learning with methods that interest learners in learning in class. Fifth, teachers have faced a lot of problems during pandemics, so they are accustomed and skilled to find solutions to every problem. Sixth, judging from the declining student grades teachers have not shown better performance in times of pandemics